How Becoming Lean Can Improve Performance: A Study on Bangladeshi Garment Industry - Ferdousi, Farhana; Ahmed, Amir (Prabandhan: Indian Journal of Management, 2010)
In this article the researchers would like to discuss two basic points: Why lean production systems becoming increasingly important as a technique to improve organizational performance and how two Bangladeshi garment firms brought changes in their traditional business process through LPS (Lean production system)."Lean production is the end point of the process leading out of the Fordist-Tailorist paradigm". Lean production places emphasis on the elimination of non-value added activity as well as waste from the production process. The goal of lean is to satisfy the customer by delivering the highest quality at the lowest cost in the shortest time (Manufactured Housing Research Alliance, 2005). The major purposes of the use of lean production are to increase productivity, improve product quality and manufacturing cycle time, reduce inventory, reduce lead time and eliminate manufacturing waste. To achieve these, the lean production philosophy uses several concepts such as one-piece flow, kaizen, cellular manufacturing, synchronous manufacturing, inventory management, pokayoke, standardized work, work place organization, and scrap reduction to reduce manufacturing waste (Russell and Taylor, 1999). In lean production systems attempts are made to eliminate waste through continuous improvement of processes of the entire value chain in the organization. Having nurtured a lean manufacturing mindset among the employees, it facilitates achievement of continuous product flow through physical rearrangement and control mechanisms. A study (Sohal, 1996, p.91) indicates that "most western manufacturers have been aware of the need to improve their performance and competitiveness for nearly two decades".